Estado actual de la comercialización del carbón vegetal en la ciudad de Iquitos, Loreto, Perú - 2021 - Villanueva Ahuanari, Melissa Cristina (2022)
The present research work was carried out in the city of Iquitos, province of Maynas in the department of Loreto, in order to determine the current state of charcoal marketing in the city of Iquitos. The research is qualitative - descriptive. According to the results obtained, it can be indicated that the activity of charcoal production and marketing is an illegal activity, 100% of the people who develop this activity do not have authorizations. Charcoal is currently marketed in different points of sale such as the Belén-Venecia market 30%, Belén-José Gálvez 25%, Puerto de productores 25% and Morona Cocha 20%. There are 37 species used for charcoal production, 11 of which account for 61.23% and the remaining 26 species account for 38.77%, which are used infrequently. The “Cumala” (virola sp.) species is the one with the highest use and occupies 13,27% of the total in terms of greater use, then the “Huira caspi” (tapirira guianensis) and “Aceite caspi” (schefflera morototoni) species reach 8,16% each, the “cético” (Cecropia spp) in a fourth place with 6,12%. The charcoal that is commercialized in the city of Iquitos comes from the different Amazon basins such as: Rio Itaya 16,58%, Rio Amazonas 15,71%, Rio Tahuayo 11,65% Rio Momon 12,81%, from some villages such as Santa Rita 6,45% Iquitos - Nauta highway 17,30% Manacamiri 9.20% and Tamshiyacu 10,30%.